EVALUATION OF CAD-INTEGRATED BUILDING ENERGY SIMULATION TOOLS FOR THE EARLY DESIGN STAGE - W., Sundoro,; M., Sudibyo, (Soegijapranata Catholic University, 2025)
The background of this study lies in the urgent need for building energy simulation (BES) tools that can be used by architects during the early design stage to support the achievement of nearly zero-energy buildings (nZEB) targets. This research aims to identify and evaluate CAD-integrated BES tools that are suitable for the conceptual design phase of buildings within the Swedish context. The methodology includes a literature review, screening of BES tools, testing on a Stockholmshus case using industry-standard values, and multi-criteria analysis through the Delphi method. The results indicate that EcoDesigner (ArchiCAD), Energy Evaluation, designPH (SketchUp), and Sefaira are the most relevant tools, although limitations persist regarding simulation assumptions, result consistency, and compliance with local regulations. The findings highlight the need for model calibration and further development to enhance the reliability of energy simulation outcomes during the early design stage.